2019
DOI: 10.1017/wet.2019.72
|View full text |Cite
|
Sign up to set email alerts
|

Control of thiocarbamate-resistant rigid ryegrass (Lolium rigidum) in wheat in southern Australia

Abstract: Two field experiments were conducted during 2018 at Paskeville and Arthurton, South Australia, to identify effective herbicide options for the control of thiocarbamate-resistant rigid ryegrass in wheat. Dose–response experiments confirmed resistance in both field populations (T1 and A18) of rigid ryegrass to triallate, prosulfocarb, trifluralin, and pyroxasulfone. T1 and A18 were 17.9- and 20-fold more resistant to triallate than susceptible SLR4. The level of resistance detected in T1 to prosulfocarb (5.9-fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…A very recent survey study, with samples collected across the whole Australian cropping system, has re‐confirmed a much lower (up to 10‐fold lower) frequency of resistance to herbicide mixtures in L. rigidum populations highly resistant to trifluralin (Busi R and Beckie HJ, unpublished). Recent field studies and historical field surveys have consistently indicated that herbicide mixtures and combinations of herbicide MOA are deliberately chosen by farmers to effectively diversify the inherent selection pressure of herbicidal weed control operations (Brunton et al ., 2020a; Harries et al ., 2020). The current use of PRE herbicides to control L. rigidum include at least five MOA, with a few more of recent introduction (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A very recent survey study, with samples collected across the whole Australian cropping system, has re‐confirmed a much lower (up to 10‐fold lower) frequency of resistance to herbicide mixtures in L. rigidum populations highly resistant to trifluralin (Busi R and Beckie HJ, unpublished). Recent field studies and historical field surveys have consistently indicated that herbicide mixtures and combinations of herbicide MOA are deliberately chosen by farmers to effectively diversify the inherent selection pressure of herbicidal weed control operations (Brunton et al ., 2020a; Harries et al ., 2020). The current use of PRE herbicides to control L. rigidum include at least five MOA, with a few more of recent introduction (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…As the use of herbicide mixtures (pre-formulated and/or 'tank' mixtures) has become an increasingly common practice (i.e. the (Brunton et al, 2020a;Harries et al, 2020). The cation (Yuan et al, 2007;Busi et al, 2014;Yu and Powles, 2014;Brunton et al, 2020b).…”
Section: Greater Efficacy Of Pre Mixturesmentioning
confidence: 99%
“…Applying a non-selective herbicide near to the time of crop maturity, commonly known as crop-topping, is also practiced in Australia. If used correctly, crop-topping can control weed survivors and significantly reduce seed viability and seedset in annual ryegrass [ 51 , 88 , 94 ]. Currently, paraquat, diquat and glyphosate are used as crop-topping agents to control the annual ryegrass seedset close to harvest in many pulse crops.…”
Section: Managementmentioning
confidence: 99%
“…Overall, in Australian grain cropping systems, herbicides of distinct groups are often used in tandem and applied sequentially to target annual ryegrass from pre-sowing to seedset [ 51 , 95 ]. Also, there has been a trend of using herbicide mixtures and rotating herbicides from different modes of action within or between seasons to control annual ryegrass and to delay the evolution of herbicide resistance [ 94 , 96 , 97 ].…”
Section: Managementmentioning
confidence: 99%
“…Research into the possibility of L. rigidum evolving resistance to more diverse SOA herbicides has provided some understanding of the likelihood of resistance evolution to herbicides not yet discovered (Busi et al 2012). The current practice of managing L. rigidum in Australia in wheat (Triticum aestivum L.) relies heavily on the use of PRE herbicides, including trifluralin (3 (K1) : inhibitors of microtubule assembly), prosulfocarb, and pyroxasulfone (Boutsalis et al 2014;Brunton et al 2020a). A greater reliance has been placed on PRE herbicides due to significant and widespread resistance to the herbicides diclofop-methyl (1 (A) : inhibitors of acetyl CoA carboxylase) and chlorsulfuron (2 (B) : inhibitors of acetolactate synthase) (Broster and Pratley 2006).…”
Section: Introductionmentioning
confidence: 99%